Some can whistle a novel - McMurtry, Larry 1936-2021 (Simon and Schuster, 1989)
Danny Deck, a middle-aged Texas writer, finds his peaceful life overturned by the arrival of T.R., the daughter he has never seen, her two children, and her two lovers--Muddy, a failed cat burglar, and Earl Dee, a dangerous psychopath.